Integrasi Pendidikan Multikultural dalam Pembelajaran Pendidikan Agama Islam (PAI) untuk Membentuk Karakter Toleran - Lindayani, Arnila; Ahmad Faturrohman, Asep; Helmawati, Helmawati (An-nida: Jurnal Pendidikan Islam, 2022)
Islamic religious education is education that is more directed at improving mental attitudes that are manifested in deeds, both for the needs of oneself and others, both theoretical and practical. This study aims to describe or explain the integration of multicultural education in Islamic religious education (PAI) learning to form a tolerant character at SDN 037 Sabang Bandung with a research focus: 1) What are the forms of integration of multicultural education in learning Islamic religious education at SDN 037 Sabang Bandung? ; 2) How is the implementation of the integration of multicultural education in learning Islamic religious education at SDN 037 Sabang Bandung?; 3) What is the impact of the integration of multicultural education in learning Islamic religious education in forming tolerance at SDN 037 Sabang Bandung?. This research method uses a qualitative type with a descriptive approach. Data collection methods used are observation, interviews and documentation. The conclusions of this study are: 1) The form of integration of multicultural education in learning Islamic religious education at SDN 037 Sabang Bandung there are six forms of integrated multicultural values in learning Islamic religious education at SDN 037 Sabang Bandung, the six forms of values are inclusive values, humanist values, values of tolerance, values of mutual assistance, democracy and ukhuwah. 2) The implementation of the integration of multicultural education in learning Islamic religious education at SDN 037 Sabang Bandung is carried out in learning planning, learning implementation, learning evaluation. 3) The impact of multicultural education in Islamic religious learning (PAI) in forming a tolerant character at SDN 037 Sabang Bandung, including: a) Creating a comfortable and conducive learning atmosphere; b) School activities run smoothly and have a high tolerance; c) The realization of religious harmony and harmony in diversity; d) Avoiding conflicts and divisions; e) The creation of a culture of mutual respect, respect and acceptance of differences.